Flow regulation increases food-chain length through omnivory mechanisms in a Mediterranean river network - Ruhí, A; Muñoz, I; Tornés, E; Batalla, R; Vericat, D; Ponsatí, L; Acuña, V; von Schiller, D; Marcé, R; Bussi, G; Francés, F; Sabater, S (Wiley, 2016)
1. Dams fragment river systems worldwide, and Mediterranean-climate rivers, characterized by highly-seasonal hydrographs and adapted biotas, areparticularly impacted by flow regulation. Whereas the effects of flow regulation on hydrology, sediment transport and biodiversity have long been examined, responses at the food-web level remain understudied. 2. Environmental variation is a key control of food-web structure. Thus, we predicted that flow regulation would impact food chain length (FCL) viachanges in the flow variation regime, and we tested this prediction in a set of flow-unregulated- to completely regulated reaches in a Mediterranean river basin. <p3. (productivity="" allowed="" and="" bayesian="" carbon="" chain="" characterized="" combined="" community="" consumers.<="" controls="" data="" dietary="" each="" estimate="" estimating="" fcl="" flow="" food="" habitat="" in="" isotopes="" length,="" mixing="" models="" nitrogen="" of="" other="" p="" proportions="" putative="" reach="" size).="" stable="" to="" together="" two="" variation,="" we="" with=""> 4. Flow variation was paramount in controlling FCL in the studied river network, and this same control largely explained the degree of top predators’ omnivory. Thus, omnivory mechanisms were the main proximate structural mechanism allowing shifts in food-web structure and linking disturbance regimes to FCL. 5. Our results suggest that flow regulation in Mediterranean rivers may impact food-web structure even when no significant changes in community composition are observed. If highly-variable Mediterranean streams become increasingly muted due to flow regulation, stable conditions could enhance intraguild predation and thus lengthen riverine food chains. </p3.>